2016
DOI: 10.1007/s11356-016-6586-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in wetland mesocosms receiving caffeine-enriched wastewater

Abstract: A 454 high-throughput pyrosequencing approach was used to characterize the structures of microbial communities in wetland mesocosms receiving caffeine-enriched wastewater at a concentration of 250 μg L −1. The removal efficiencies of caffeine in the planted beds (93.0 %) were significantly (p < 0.05) higher than those in the unplanted beds (81.4 %). Bacterial diversity was decreased by 25 and 22.4 %, respectively, in both planted and unplanted mesocosms after 210-day operation. The results of taxonomic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Besides being found recurrently associated with various marine invertebrates, Pseudovibrio strains have been also detected in marine and estuarine sediments, seawater, oil samples, wastewater treatment systems, and wetland mesocosms ( Fig. 1 and 2) (1,2,(12)(13)(14)(15)(16)(17)(18). An overview of the sources where Pseudovibrio strains have been detected is shown in Fig.…”
Section: Distribution Of Bacteria Belonging To the Pseudovibrio Genusmentioning
confidence: 98%
“…Besides being found recurrently associated with various marine invertebrates, Pseudovibrio strains have been also detected in marine and estuarine sediments, seawater, oil samples, wastewater treatment systems, and wetland mesocosms ( Fig. 1 and 2) (1,2,(12)(13)(14)(15)(16)(17)(18). An overview of the sources where Pseudovibrio strains have been detected is shown in Fig.…”
Section: Distribution Of Bacteria Belonging To the Pseudovibrio Genusmentioning
confidence: 98%
“…Regarding the removal of organic compounds, Zhang et al (2016) used T. angustifolia in an HSSF to remove caffeine (250 μg/L), obtaining a removal efficiency by 78.5% during the experimental period (7 months). The characterization of the bacterial consortium, using culture-independent methods, revealed that sediment is colonized by great bacterial diversity that could adapt to the wetland conditions and metabolizes the compound.…”
Section: Isolation Of Cultivable Bacteria Associated With the Root Of Typha Latifoliamentioning
confidence: 99%
“…It has been demonstrated that S. maltophilia KB2 transforms naproxen, obtaining 28% of removal after 35 days of incubation in the Mueller Hinton Broth (MHB) supplemented with 6 mg/L of naproxen (Gren et al 2010). Zhang et al (2016) conducted a study within a subsurface flow wetland planted with Typha angustifolia, which was employed to treat an effluent contaminated with 250 μg/L of caffeine, demonstrating that T. angustifolia removed caffeine with an efficiency of 93%. Moreover, characterization of non-cultivable bacterial communities associated with the roots of T. angustifolia revealed that plant is colonized with at least 20 phyla, among which the most predominant were Firmicutes (39.0%), Actinobacteria (25.1%), and Proteobacteria (17.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies attempted to explore the bacterial communities associated with wetland plants and even fewer to describe the responses of such communities to mixed and highly polluted environments ( Su et al, 2015 ; Zhao et al, 2015 ; Zhang D. et al, 2016 ; Syranidou et al, 2017b ). Moreover, information relevant to the impacts of pollutants on the endophytic bacteria of wetland plants is scarce.…”
Section: Introductionmentioning
confidence: 99%